Results of a case study on the application of automated fiber placement for a helicopter airframe structure - Eberth, U.; Wolters, L. (My University, 2015)
Due to economic and ecologic reasons a number of different technologies for the automated layup of composite parts for H/C airframe structures are currently evaluated. Automated Fiber Placement (AFP) is one of the promising technologies as it shows appropriate characteristics to lay-up fiber material over three-dimensional curved tooling-surfaces and in particular over sandwich areas for helicopter shell elements, due to its capability of laying-up individual narrow prepreg tows. As today's field of AFP application is focused on monolithic parts a study was carried out to evaluate and optimize all relevant parameter along the process chain for a H/C bottom shell in sandwich design. The key potential of the technology was found in a considerably higher layup rate compared to manual layup and more consistent part quality as well as largely reduced scrap rates.
Keywords: Structures & Materials